Glycolysis, monocarboxylate transport, and purinergic signaling are key events in Eimeria bovis-induced NETosis - Conejeros, Iván; López-Osorio, Sara; Zhou, Ershun; Velásquez, Zahady D.; Del Río, María Cristina; Burgos, Rafael Agustín; Alarcón, Pablo; Chaparro-Gutiérrez, Jenny Jovana; Hermosilla, Carlos; Taubert, Anja (Frontiers in Immunology, 2022)
The protozoan parasite Eimeria bovis is the causative agent of bovine coccidiosis, an enteric disease of global importance that significantly affects cattle productivity. Previous studies showed that bovine NETosis, - an important early host innate effector mechanism of PMN- is elicited by E. bovis stages. So far, the metabolic requirements of E. bovis-triggered NETs formation are unknown. We here studied early glycolytic and mitochondrial responses of PMN as well as the role of pH, distinct metabolic pathways, P2 receptor-mediated purinergic signalling and monocarboxylate transporters 1 and 2 (MCT-1, MCT-2) in E. bovis sporozoite-induced NET formation. Seahorse-based experiments revealed a rapid induction of both neutrophil oxygen consumption rates (OCR) and early glycolytic responses thereby reflecting immediate PMN activation and metabolic changes upon confrontation with sporozoites. The impact of these metabolic changes on NET formation was studied via chemical inhibition experiments targeting glycolysis and energy generation by the use of 2-fluor-2-deoxy-D-glucose (FDG), 6-diazo-5-oxo-L-norleucin (DON), sodium dichloroacetate (DCA), oxythiamine (OT), sodium oxamate (OXA) and oligomycin A (OmA) to block glycolysis, glutaminolysis, pyruvate dehydrogenase kinase, pyruvate dehydrogenase, lactate dehydrogenase and mitochondrial ATP-synthase, respectively. Overall, sporozoite-induced NET formation was significantly diminished via PMN pre-treatments with OmA and OXA, thereby indicating a key role of ATP- and lactate-mediated metabolic pathways. Consequently, we additionally studied the effects of extracellular pH, MCT-1, MCT-2 and purinergic receptor inhibitors (AR-C141900, AR-C155858, theobromine and NF449, respectively). Pre-treatment with the latter inhibitors led to blockage of sporozoite-triggered DNA release from exposed bovine PMN. This report provides first evidence on pivotal role of carbohydrate-related metabolic pathways and purinergic receptors being involved in E. bovis sporozoite-induced NETosis.